(untitled) (Research, Society and Development, 2020)
Ivermectin (IVM) is a drug derived from avermectin B1 with high permeability and low solubility. It is used as a broad spectrum antiparasitic and studies reveal promising antiviral and anti-inflammatory activities. In addition, formulations and delivery systems have been applied to optimize the solubility and bioavailability of the drug. Thus, it is intended to highlight the development of new formulations and delivery systems containing IVM in view of not only the technological benefits, but also the benefits of effectiveness in the face of distinct disorders for which the drug was not originally applied. The delivery systems have been applied to optimize the solubility and bioavailability of IVM, reduce its cytotoxicity and increase the therapeutic effect in smaller doses. In this sense, the literature reveals different formulations and delivery systems containing IVM that aim to improve their physical-chemical properties, such as microparticles, microspheres, liposomes, microemulsions, in situ formation gel, controlled and prolonged release formulations, solid dispersion and micelles mixed. As a potential antiviral agent, this drug inhibits the replication of viral strains and reduces serum levels of viral protein in in vitro and in vivo studies; when incorporated into liposomes, efficacy was high and toxicity reduced. IVM has shown potential for application in dermatological disorders due to anti-inflammatory activity, highlighting the successful repositioning for the treatment of papulopustular rosacea. Therefore, repositioning older drugs to treat common or rare diseases, as well as in the face of an urgent need, becomes an attractive tool in the scope of drug research and development.